Evaluation of Achievement Development Programs in Football School Clubs (SSB) in Semarang City - Rifqi Firdaus Rahmayanto; ipang setiawan; Mugiyo hartono (Journal of Physical Education and Sports, 2026)
Competition to promote sports in each region is getting tighter, especially in football at an early age, this makes there are problems in coaching achievements, namely related to consistency, decline, and increase in achieving and fostering achievements in a football school club in Semarang. This study aims to provide a review of the evaluation of achievement development program which is one of the important factors for achievement in fostering a football club by using the CIPP model evaluation (context, input, process and product). This research method uses qualitative methods by providing interviews to resource persons, observations about the club, and documentation with the subjects of research are new Star FA club, SSS Semarang, New Tugu Muda, and Indonesia Muda FA. The findings showed that in the context aspect, all clubs have coaching goals that are aligned with the vision of improving achievement, although documentation and strategic planning are still not maximized in some clubs. In the input aspect, most clubs already have certified coaches and basic training programs, but are still constrained in funding, infrastructure, and HR support. In the process aspect, the implementation of the training program runs on schedule, but not entirely based on periodization-based planning. On the product aspect, achievements between clubs vary. The conclusion of this study is that the achievement development program at the SSB club in Semarang has been running quite well, but still requires strengthening in terms of planning management, supporting resources, and ongoing evaluation.